Community perceptions of the development of natural attractions in the central buton district - Tajriani, Nani; Gazalin, Junaid; Inzana, Nur (Institute Of computer Science (IOCS), 2024)
This type of research is a type of qualitative research where this method can also be used to gain insight into something that is only slightly known, and can help researchers provide complex details about phenomena that are difficult to reveal. The analysis technique used in this research is through the following stages; Conducting data review, namely in the form of a comprehensive presentation of data results, both from interviews and documentation, (Data reduction, Compilation into units, Categorization, Data validity checking, namely efforts to determine whether the incoming data meets the research requirements or not, so that if not, it can be refined, and data analysis and interpretation. The results of this research are A) Public Perception of Tourism Objects. 1) The development of tourist attractions in Central Buton Regency has not been maximized because there are still tourist attractions visited by severe visitors who always complain about the attractions visited. Tourism in terms of introducing cultural tourism to visitors or the local community is quite good, because the tourism office always introduces through social media and through festivals organized by the Central Buton Regency government. B) Factors that Support Optimizing the Role of the Tourism Office in Central Buton Regency. Basically, the availability of facilities and infrastructure at the Central Buton Regency Tourism Culture Office is sufficient, starting from basic facilities such as telephones, vehicles, computers, and so on, which are considered sufficient in order to support the role of the Central Buton Regency Youth Tourism Culture Office in tourism development 2) less able to compete with tourism in other areas, one of which is about the lack of public awareness related to tourism development in their area